A Practicable Guideline for Predicting the Thermal Conductivity of Unconsolidated Soils - Bertermann, David; Rammler, Mario; Wernsdorfer, Mark; Hagenauer, Hannes (Soil Systems, 2024)
For large infrastructure projects, such as high-voltage underground cables or for evaluating the very shallow geothermal potential (vSGP) of small-scale horizontal geothermal systems, large-scale geothermal collector systems (LSCs), and fifth generation low temperature district heating and cooling networks (5GDHC), the thermal conductivity (λ) of the subsurface is a decisive soil parameter in terms of dimensioning and design. In the planning phase, when direct measurements of the thermal conductivity are not yet available or possible, λ must therefore often be estimated. Various empirical literature models can be used for this purpose, based on the knowledge of bulk density, moisture content, and grain size distribution. In this study, selected models were validated using 59 series of thermal conductivity measurements performed on soil samples taken from different sites in Germany. By considering different soil texture and moisture categories, a practicable guideline in the form of a decision tree, employed by empirical models to calculate the thermal conductivity of unconsolidated soils, was developed. The Hu et al. (2001) model showed the smallest deviations from the measured values for clayey and silty soils, with an RMSE value of 0.20 W/(m∙K). The Markert et al. (2017) model was determined to be the best-fitting model for sandy soils, with an RMSE value of 0.29 W/(m∙K).
CRIS-Team Scopus Importer:2024-07-05
Keywords: fifth generation low temperature district heating and cooling networks (5GDHC); high-voltage underground cables; large-scale geothermal collector system (LSC); model validation; thermal conductivity of soils; very shallow geothermal potential (vSGP)

Comparison of Measured and Derived Thermal Conductivities in the Unsaturated Soil Zone of a Large-Scale Geothermal Collector System (LSC) - Rammler, Mario; Schwarz, Hans; Wagner, Jan; Bertermann, David (Energies, 2023)
The design, energetic performance, and thermal impact of large-scale geothermal collector systems (LSCs) are dependent on the thermal conductivity of unsaturated soils (λ). The aim of this study was to investigate the benefits of two different λ measurement methods using single-needle sensor measuring devices on a laboratory scale. Since large-scale determinations are required in the context of LSCs, the potential for deriving λ from electrical resistivity tomography measurements (ERTs) was also examined. Using two approaches—the continuous evaporation method and the punctual method—thermal conductivities of soil samples from Bad Nauheim (Germany) were measured. The results were compared with averaged λ derived from three ERT sections. With the evaporation method, significant bulk density changes were observed during the experimental procedure, which were caused by the clay content and the use of repacked samples. The punctual method ensures a sufficiently constant bulk density during the measurements, but only provides a small number of measurement points. The thermal conductivities derived from ERTs show largely minor deviations from the laboratory measurements on average. If further research confirms the results of this study, ERTs could provide a non-invasive and unelaborate thermal exploration of the subsurface in the context of large-scale infrastructure projects such as LSCs.<br
Keywords: large-scale geothermal collector system (LSC); thermal conductivity of soils; single-needle sensor; electrical resistivity tomography (ERT); shrinkage of soils; unsaturated soil zone

Groundwater temperatures downstream from a large-scale geothermal collector system (LSC) in Bad Nauheim, Germany - Rammler, Mario; Bertermann, David (Grundwasser, 2025)
The impact of horizontal geothermal systems on groundwater temperature has not been studied in detail due to their generally shallow installation depth. However, interactions between very shallow geothermal systems and groundwater are expected, especially at short groundwater distances. In this study, the effects of a large-scale geothermal collector system (LSC) in Bad Nauheim (Hesse, Germany) on the downstream shallow groundwater were analysed. For this purpose, subsurface and groundwater temperatures were measured over a period of two years. The results showed that in the immediate downstream area, the maximum degree of cooling of the groundwater temperature was between 4.2 and 5.2 K with a minimum temperature of 5.2 °C. Consequently, the presence of a temperature plume was demonstrated, whereby a significant regeneration of the subsurface temperature in comparison to measured values within the LSC area was also observed.
CRIS-Team Scopus Importer:2025-02-14
Keywords: Groundwater monitoring; Groundwater temperature; Large-scale geothermal collector system (LSC); Temperature plume

Influence of Groundwater on the Very Shallow Geothermal Potential (vSGP) in the Area of a Large-Scale Geothermal Collector System (LSC) - Rammler, Mario; Zeh, Robin; Bertermann, David (Geosciences, 2023)
The water balance in the very shallow subsurface can be influenced by capillary rise due to a high groundwater table. Since moisture content is an important factor for the thermal conductivity of soils, this can also have an influence on the very shallow geothermal potential (vSGP). For this reason, the effect of spatial and seasonal variations in groundwater tables on moisture content in essential depth layers was investigated at a large-scale geothermal collector system (LSC) in Bad Nauheim, Germany. Quasi-one-dimensional simulations using the FEFLOW® finite-element simulation system were employed to determine site-dependent and seasonally varying moisture contents, from which thermal conductivities were derived. The model setup was previously validated based on recorded moisture contents. The simulations resulted in groundwater-related maximum seasonal and spatial differences in thermal conductivity of 0.14 W/(m∙K) in the LSC area. Larger differences of up to 0.21 W/(m∙K) resulted for different soil textures at the same depth due to different thermal properties. The results indicate that an efficient design of LSCs requires a sufficiently detailed subsurface exploration to account for small-scale variations in grain size distribution and groundwater level.
CRIS-Team Scopus Importer:2023-09-08
Keywords: groundwater; large-scale geothermal collector system (LSC); quasi-one-dimensional simulation; thermal conductivity of soils; very shallow geothermal potential (vSGP)

Investigation of the influence of groundwater flow on horizontal ground heat exchangers using numerical simulations - Rammler, Mario; Suft, Oliver; Bertermann, David (Hydrological Research Letters, 2025)
In contrast to unsaturated soil conditions, advective heat transport dominates in aquifers. Consequently, groundwater flow can affect the efficiency of geothermal horizontal ground heat exchangers (HGHEs) and the development of downstream thermal plumes. In contrast to deeper geothermal systems, this has not been investigated in detail for HGHEs due to their shallow installation depths. In order to address this issue, in this study, the effects of different groundwater flow conditions on a theoretical unidirectional HGHE were evaluated using the FEFLOW® finite element simulation system. A total of 81 variants with different groundwater levels, flow velocities and flow directions were considered in the numerical simulations. The results showed a significant increase in HGHE efficiency with increasing groundwater level (GWL) and flow velocity. In addition, significantly higher heat gains were obtained when the groundwater flow direction was orthogonal to the HGHE. The lateral spread of the thermal plumes was greatest for orthogonal flow directions, high flow velocities and groundwater levels slightly above the HGHE. The presented FEFLOW® approach was suitable to investigate the effects of different hydraulic subsurface conditions on a unidirectional HGHE and should be vali-dated with real measured data in further research.
CRIS-Team Scopus Importer:2025-03-28
Keywords: advective heat transport; FEFLOW®; groundwater; horizontal ground heat exchangers; numerical simulations

Mapping of Very Shallow Geothermal Potentials in Rural Areas: a Case Study of Bavaria (Germany) - Bertermann, David; Jocic, Nikola; Rammler, Mario; Schwarz, Hans; Wagner, Jan (Alternative Energy Sources, Materials and Technologies (AESMT’21), 2021)
Shallow geothermal energy is a renewable source for heating and cooling systems and buildings, by which a significant part of the arising energy demand could be covered if it is in widespread use. Especially in rural areas (very) shallow geothermal systems are well applicable due to the availability of spacious unsealed areas. The aim of the study was the examination of geothermal potential maps for utilization of very shallow horizontal applications in the rural areas of Bavaria (Germany). These potential maps should bring a more facilitated access to this issue for heating engineers and planners and with that a more common use of shallow geothermal energy. To develop these potential maps, the relevant parameters were implemented as areal data in a geographical information system (GIS). As database serves a soil map of Bavaria (scale 1:5000) which includes crucial parameters such as soil texture. Additionally, climate data based on degree-day numbers for characteristic regions were implemented. Soil and climate data provided the basis to develop an algorithm for calculation of (very) shallow geothermal potentials. Results are presented in two categories – thermal conductivity on the one hand, and heat extraction on the other. Thermal conductivity is the general parameter which describes local geothermal potentials, dependent on soil texture, bulk density and water content, while heat extraction is given as a system-specific characteristic. This research focused on four different shallow geothermal systems – horizonal ground heat collectors, capillary tube mats, geothermal baskets, and trench collectors. These geothermal potentials were processed in a GIS project enabling the output as potential maps. For validation of the very shallow geothermal potential maps soil data from selected case study municipalities were consulted. Therefore, data from geotechnical surveys and sampled and analysed soils were used. As a result, these maps revealing the very shallow geothermal potential can serve as handy tool for heating engineers and planners for an appropriate design of these horizontal geothermal applications. Afterall, the compilation process is easy to transfer to other regions, just by using respective soil maps and climatic dat
Keywords: Very shallow geothermal potential (vSGP); thermal conductivity; heat extraction; geothermal potential maps; GIS; rural areas

Mapping of very shallow geothermal potentials in rural areas of Bavaria - Bertermann, David; Schwarz, Hans; Rammler, Mario; Jocic, Nikola (Glasnik Srpskog Geografskog Društva, 2024)
Climate change is a rising issue which strongly influences contemporary society. Therefore, the utilization of sustainable non-fossil energy sources is one of the most important goals in order to reduce greenhouse gas emission. Utilization of geothermal energy for heating and cooling buildings or residential units is one of the significant steps in providing sustainable and renewable energy supply. This paper presents very Shallow Geo-thermal Potentials (vSGP) of German federal state Bavaria, with special focus on rural are-as. Main goal of the study was to analyze the potentials for utilization of very shallow geo-thermal systems in terms of thermal conductivity and heat extraction. High-resolution soil maps containing information of grain size conditions served as an area-wide data basis for the research, while the analysis and visualization of the results were conducted by GIS software. Thermal conductivity as well as system-specific heat extraction were calculated depending on soil texture and climate conditions. Thermal conductivity results are intend-ed to be further used as the basic parameter for planning and installing horizontal geo-thermal heating and cooling systems.<br
Keywords: very shallow geothermal potentials (vSGP); thermal conductivity; heat extraction; sustainable cooling; rural area; Bavaria

Suitability of Screened Monitoring Wells for Temperature Measurements Regarding Large-Scale Geothermal Collector Systems - Bertermann, David; Rammler, Mario (Geosciences, 2022)
Groundwater temperature (GWT) is usually measured using screened monitoring wells (MWs). The aim of this study was to investigate whether MWs are suitable for monitoring the effects of large-scale geothermal collector systems (LSCs) on GWT, focusing on possible vertical flows within the MWs due to both natural and forced convection. Comparative temperature depth profiles were therefore recorded over a period of nine months in both shallow MWs and in small-diameter, non-screened temperature monitoring stations (TMSs), each of which was installed in a single borehole. Particularly high temperature deviations were measured in MWs in the upper part of the water column where the GWT reached up to 1.8 K warmer than in the surrounding subsurface. These deviations correlate unambiguously with the prevailing positive thermal gradients and are caused by thermal convection. Where forced convection occurred, the GWT was measured to be up to 0.8 K colder. Potential temperature deviations must be considered when monitoring very shallow GWT as thermal gradients can be particularly high in these zones. For monitoring concepts of LSCs, a combination of MW and TMS is proposed for GWT measurements decoupled by the effects of convection and in order to enable further investigations such as pumping tests.
CRIS-Team Scopus Importer:2022-05-06
Keywords: convection; groundwater temperature; hydrogeology; large-scale geothermal collector (LSC); monitoring well; subsurface